Editorial - Nain, Manjeet Singh (Indian Journal of Extension Education, 2023)
Editorial (July-September, 2023) Food system shocks risk increasing food insecurity, hunger, and malnutrition can disrupt livelihoods, increase poverty, and further diminish prospects for the world’s most vulnerable populations. Addressing the “new normal” of more frequent and often overlapping crises requires rethinking national and global responses that build long-term resilience. Hundreds of thousands of locusts are destroying crops in Afghanistan, a country where nine in ten families already struggle to afford food. If left unchecked, the population of locusts could increase hundred fold in the next year. El Niño conditions are compounding the already dry season in Panama and raising concerns that prices for traded goods like food will increase. The proposal for enacting of the Children’s Act for Responsible Employment (CARE), which would criminalize current agriculture labor practices that allow for children as young as 12 years old to work on farms, with no limits on labor time or farm type will threaten to long-held family practices and financial livelihood. The destruction of the Kakhovka Dam will directly affect food security, and global wheat supply concerns, increasing prices once again, also, some farmland will be completely destroyed even after the floodwaters recede. Two weeks of continuous rain in regions of China created oversaturated wheat crops and left fields too wet to harvest, causing kernels to sprout too early and consequently produce worse quality flower, the rains are significantly lowering national grain production, which may lead to higher imports and ultimately raise global food prices. The Indian Society of Extension Education (ISEE), New Delhi celebrated its 60th inception on 22 June 2023 during its National Seminar 2023 on ‘Evolving Extension Science towards Secondary Agriculture for Sustainable Development’ at the University of Agricultural Sciences, Bangalore during June 22-24, 2023. The seminar witnessed participation of over 550 scholars, 100 famers, 37 exhibitors across 25 states, 63 universities, and 17 ICAR institutes. Significant recommendations aroused for research, academia, extension professionals, policy planners, governmental and nongovernmental organizations interested in agricultural extension. The current issue (July-September, 2023) contains 31 manuscripts including two research tools, four research notes, and twenty five full-length research papers from cross-sectional authors and content. The data is regularly being fed to indexing agencies and its indexing at Index Copernicus International Journal Master list, CAB International; ICI; BASE; Google scholar; Scilit; Semantic Scholar; WorldCat; Science gate; Agricultural Science and Technology Information database of FAO, PlumX, Mendley and Crossref. From January 2023, the Indian Journal of Extension Education has been inducted into the UGC CARE List enabling the authors and scholars to quote the publications in IJEE for their personal promotions as well as accreditations for NAAC and other rankings including NIRF. I extend sincere thanks to all the expert members of the editorial board for their painstaking efforts. The reviewing contributions of not only the editorial team members but many willful contributors are sincerely acknowledged. I extend my sincere thanks to all the authors for making valuable contributions. The support extended by Executive Council is duly acknowledged. Special thanks are extended to the President, ISEE; Dr. U.S. Gautam, Secretary ISEE; Dr. Rashmi Singh, Treasurer, ISEE; Dr. B. K. Singh and Joint Secretary, ISEE; Dr. J. S. Malik for providing insightful thoughts and guidance in bringing out this issue. Dr. Bhanu P. Mishra, Vice President (Central Zone) deserves special thanks for making committed efforts at all stages of ISEE matters. (Manjeet Singh Nain)